To challenge and to be challenged – teachers collective learning in higher education. Issue 3 (4th May 2019) - Gustavsson, Susanne; Andersén, Annelie; Berglund, Mia
ABSTRACT: Critical analyzing and reflective competence are essential objectives in all higher education. In academic professional education, it is a challenge for the teacher to support and develop the student´s critical reflection of both academic and placement studies. The aim of this study is to identify the characteristics of the teacher role and the challenges of the reflective seminar within higher education. Data were gathered through group interviews and analyzed with a phenomenological hermeneutic approach. The result shows four themes; the experience of control and uncertainty, building trust and challenging ideas, the alternation between closeness and distance, and the parallel processes of supervising learning and being in a learning state. One conclusion is that the seminar teaching practice stimulates a collegial learning environment. This practice promotes the teachers pedagogical and didactical competence and an open attitude to each other´s teaching practice.